Cross-Taxon Congruence of Taxonomic and Functional Beta-Diversity Facets Across Spatial and Temporal Scales - Lansac-Tôha, Fernando Miranda; Heino, Jani; Bini, Luis Mauricio; Peláez, Oscar; Baumgartner, Matheus Tenório; Quirino, Bárbara Angélio; Pineda, Alfonso; Meira, Bianca Ramos; Florêncio, Fernanda Moreira; Oliveira, Felipe Rafael; Bomfim, Francieli Fátima; Silveira, Márcio José; et al. (Frontiers in Environmental Science, 2022)
An intensively debated issue in ecology is whether the variations in the biodiversity patterns of different biological groups are congruent in space and time. In addition, ecologists have recognized the necessity of accounting for both taxonomic and functional facets when analysing spatial and temporal congruence patterns. This study aimed to determine how the cross-taxon congruence of taxonomic and functional beta-diversity and its underlying components varies across space and time, using data from four floodplains at a subcontinental scale. Our general hypothesis was that the congruence between aquatic biological groups, either taxonomic or functional, would decrease with the “between-group” functional distance. Also, we examined how congruence patterns varied across spatial and temporal scales by focusing on how the cross-taxon relationships differ among Brazilian floodplains and between drought/flood periods. Our study comprised information on eight biological groups from the four major Neotropical river-floodplain systems, and cross-taxon congruence was assessed using Procrustes analysis. Our results show how detailed hierarchical analyses can reveal hidden patterns of cross-taxon congruence, and partially supported the hypothesis that the strength of cross-taxon congruence is negatively related to between-group functional distance.